2021
DOI: 10.1111/ijlh.13474
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the accuracy of immature granulocyte percentage in predicting pediatric serious bacterial infection

Abstract: Introduction Serious bacterial infections (SBI) are major causes of mortality and morbidity in children. The aim of this study was to determine the accuracy of the immature granulocyte (IG) percentage in predicting SBI. Methods Patients admitted to the pediatric emergency department with fever were divided into two groups: with SBI and with non‐SBI. White blood cell (WBC) count, absolute neutrophil count (ANC), C‐reactive protein (CRP), and the percentage of IG value were recorded, and their accuracy in predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 22 publications
(24 reference statements)
1
6
0
Order By: Relevance
“…As a new inflammatory marker, it is seen that IG and IG%, which are significant in neonatal sepsis and severe bacterial infections in childhood, are distinctive for adult appendicitis cases in Ünal's study (10,20,21). In our study, UA and CA It was observed that the IG and IG% of the cases were statistically significantly higher.…”
Section: Discussionsupporting
confidence: 47%
“…As a new inflammatory marker, it is seen that IG and IG%, which are significant in neonatal sepsis and severe bacterial infections in childhood, are distinctive for adult appendicitis cases in Ünal's study (10,20,21). In our study, UA and CA It was observed that the IG and IG% of the cases were statistically significantly higher.…”
Section: Discussionsupporting
confidence: 47%
“…This study aimed to develop expert consensus regarding the parameters associated with varying degrees of disease severity in pediatric CAP. They recommended using oxygen saturation and objective data to determine the severity of pneumonia (24). The study by Awasthi et al (28) emphasised that hypoxia and pneumonia in children under five years of age increase the mortality rate and may cause severe pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Studies comparing the DNI with these markers have been conducted in predicting infection. [14][15][16] In a study which evaluated the diagnostic and prognostic power of the DNI and CRP in paediatric sepsis, Nam et al found that CRP is not specific for sepsis, the DNI has the strongest prognostic power among WBC parameters, and the DNI has the most powerful diagnostic potential among the parameters tested. They found the cut-off level of the DNI for sepsis was 2.7, which is similar to ours (2.5).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, there is no perfect marker for predicting SBIs, and elevated values of the most frequently used markers, including WBC count, CRP and ANC, are not specific for SBIs. Studies comparing the DNI with these markers have been conducted in predicting infection 14–16 . In a study which evaluated the diagnostic and prognostic power of the DNI and CRP in paediatric sepsis, Nam et al .…”
Section: Discussionmentioning
confidence: 99%